Modern power electronics and AC drives - Bose, Bimal K. (Prentice Hall, 2002)
Technological advances and cost reductions have promoted electrical power applications in many areas. This title seeks to explain advanced technical topics in a clear language with figures and equations to further develop the readers understanding.